Human capital development: organizational culture context - Shavkun, Iryna; Dybchinska, Yana (Management and Entrepreneurship: Trends of Development, 2022)
In the conditions of the knowledge economy, the most important source of competitive advantages of the organization is human capital. The human capital development is based on the relevant management culture to provide proper material and technical prerequisites for motivating both high activity culture standards and productive performance. Hence efficient organizational culture of modern business environment affects almost all aspects of the organization activities and is a must for human capital formation.The need to understand the role of organizational culture as an effective strategic tool in the management of organizational processes in the modern business environment actualizes the topic of this study and determines the goal - to analyze the significance of organizational culture in transforming human potential into human capital as a social resource that makes efficient production and innovation possible.The specified goal presupposes the setting of a number of tasks to identify the essence of such concepts as "corporate culture", "human capital" and "human potential" and to analyze their interdependence in the process of functioning and development of modern business organizations.Methodology. General scientific methods are used to substantiate the theoretical positions and reasoning of the conclusions. The system method allows to consider the nature and instrumental role of organizational culture for the manager to transform the human potential into the human capital of the organization.The results of the study indicate the complex nature of the organizational culture phenomenon as a factor in the developing and managing human capital: on the one hand, it is a tool for transforming human potential into the human capital of the organization, on the other hand, it is an integral attribute of human capital itself.JEL Classification: J24, E22, M12, M14, D23, O 15